2020
DOI: 10.1016/j.foreco.2019.117635
|View full text |Cite|
|
Sign up to set email alerts
|

Biochar addition to forest plantation soil enhances phosphorus availability and soil bacterial community diversity

Abstract: Depletion of soil nutrients is a major cause of decline in productivity of forest plantations in successive rotations. Biochar amendment in agricultural systems has been shown to yield various beneficial effects, including increasing soil phosphorus (P) availability. However, the direct and indirect effects of biochar addition on forest soil P dynamics have largely been unexplored. The objective of this study was to examine how biochar produced from harvest residue (leaves and woodchips) affect the P dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Moreover, there is no difference among all CSB treatments ( Figure 2C). Similar results were also reported in previous studies [82][83][84]. After 180 days incubation, 3CSB300 and 5CSB300 resulted in an increase of the enzyme activities by 25.13% and 14.47% over control in the purple soil, respectively.…”
Section: Csb Effects On Soils Microbial Propertiessupporting
confidence: 91%
“…Moreover, there is no difference among all CSB treatments ( Figure 2C). Similar results were also reported in previous studies [82][83][84]. After 180 days incubation, 3CSB300 and 5CSB300 resulted in an increase of the enzyme activities by 25.13% and 14.47% over control in the purple soil, respectively.…”
Section: Csb Effects On Soils Microbial Propertiessupporting
confidence: 91%
“…Fe-oxides). Introducing dissolved organic matter into soils is known to reduce soil P fixation through competing for sorption sites, forming chelates between cations, such as Fe 3+ and Al 3+ , and organic molecules [78], and enhancing electrostatic repulsive forces [72]. Therefore, the P release observed in the study performed by Schneider and Hederlein [72] was most likely caused by the negatively charged organic matter derived from biochar, which reduced P sorption on goethite in addition to increase the soil pH.…”
Section: Change In the P Fixation Mechanism In Soils By Biochar Amendmentioning
confidence: 94%
“…Similarly, a greenhouse study concluded that biochar improved soil enzymatic properties with the application rate up to 6% (Yadav et al 2018). Biochar also increased P-solubilizing bacterial populations such as Burkholderia-Paraburkholderia, Planctomyces, Sphingomonas, and Singulisphaera, which contributed to improving P availability in a forest soil (mountain acidic red loam soil) (Zhou et al 2020). However, Haefele et al (2011) found a negative effect on earthworm populations with the addition of rice residue biochar (41.3 Mg ha −1 ).…”
Section: Biological Propertiesmentioning
confidence: 96%